PENGARUH LIKUIDITAS, LEVERAGE DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Artanti, Ratna Ari; Rahmiyati, Nekky (PRIMA EKONOMIKA, 2022)
This observe objectives to investigate the impact of liquidity, leverage, capital shape on organization price and profitability as intervening variables. This observe makes use of a pattern of Textile and Garment businesses indexed at the Indonesia Stock Exchange (IDX), yearly for 3 years, from 2019 to 2021. The statistical approach used on this observe is Partial Least Square (PLS). The effects confirmed that liquidity had no enormous impact on organization price, liquidity had no enormous impact on organization price, leverage had no enormous impact on organization price, leverage had no enormous impact on profitability, capital shape had no enormous impact on organization price, and capital shape had no enormous impact on profitability. , Profitability has enormous impact at the price of the company. Keywords: Liquidity, Leverage, Capital structure, firm value, profitability